2016
DOI: 10.1016/j.athoracsur.2016.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Atrial Fibrillation on Postoperative Thromboembolic Events After Left Ventricular Assist Device Implantation

Abstract: Preoperative AF was associated with a similar incidence of postoperative stroke, device thrombosis, and survival. On the basis of these data, it seems unnecessary to perform a left atrial appendage ligation or to alter postoperative anticoagulation in patients with AF undergoing LVAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…(11,26) We did not find a history of atrial arrhythmias to be a predictor for stroke. Therefore, data don’t support routine intensification of anticoagulation or adjunctive procedures such as left atrial appendage ligation or Maze procedure during LVAD implant in patients with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 63%
“…(11,26) We did not find a history of atrial arrhythmias to be a predictor for stroke. Therefore, data don’t support routine intensification of anticoagulation or adjunctive procedures such as left atrial appendage ligation or Maze procedure during LVAD implant in patients with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 63%
“…To explain an increase in the mortality rate of AF group, we also looked at the incidence of right heart failure among the study population. There is no significant difference in perioperative/postoperative right heart failure incidence between AF and non‐AF groups in three studies . Interestingly, among those studies, Oezpeker and team also reported a significantly higher incidence of right heart failure as a cause of death in AF group compared to NAF group (21.4% vs. 10.2%).…”
Section: Discussionmentioning
confidence: 85%
“…There is no significant difference in perioperative/postoperative right heart failure incidence between AF and non-AF groups in three studies. 14,17,18 Interestingly, among those studies, Oezpeker and team 14 also reported a significantly higher incidence of right heart failure as a cause of death in AF group compared to NAF group Another interesting observation is that only certain subtypes of atrial fibrillation are associated with an increased mortality rate in this population. In a multivariate regression analysis, Enriquez et al 13 found that persistent AF is an independent predictor for a composite endpoint of death or heart failure hospitalization.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations